2008
DOI: 10.1039/b719017d
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic anilido-aldimine Al or Zn complexes for efficient ring-opening polymerization of ε-caprolactone

Abstract: Four bimetallic Al or Zn complexes supported by anilido-aldimine ligands (o-C6H4(NHAr)-CH=N)2CH2CH2 (Ar = 2,6-Me2C6H3,L1H2; Ar = 2,6-iPr2C6H3, L2H2) have been synthesized and characterized. Treatment of L1H2 or L2H2 with two equiv. of AlMe3 gives bimetallic complex L1(AlMe2)2 1 or L2 (AlMe2)2 2, respectively. Reaction of L1H2 or L2H2 with two equiv. of ZnEt2 leads to bimetallic complex L1(ZnEt)2 3 or L2(ZnEt)2 4, respectively. All of the complexes 1-4 are efficient catalysts for ring-opening polymerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 82 publications
5
60
0
Order By: Relevance
“…First, we examined the effect of temperature and solvent for the polymerization, Table 1 (entries 1,[5][6][7][8]. It was found that the higher the temperature was, the faster the polymerization proceeded (Table 1, entries 1, 5-8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, we examined the effect of temperature and solvent for the polymerization, Table 1 (entries 1,[5][6][7][8]. It was found that the higher the temperature was, the faster the polymerization proceeded (Table 1, entries 1, 5-8).…”
mentioning
confidence: 99%
“…PCL is usually prepared by the ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) initiated by metal complexes [1]. Among the reported initiators, organoaluminum complexes have attracted much attention because they have a good control over the polymerization reaction [7] and low toxicity [8]. However, few studies have involved the alkyl aluminum complexes as the initiator for the ROP of ε-CL without the presence of alcohol, because these complexes usually showed no or very low activity towards this polymerization [9], and most of them got a broad molecular weight distribution during the reaction [9,10].…”
mentioning
confidence: 99%
“…Proligands 1e4 were synthesized by modifying previously reported procedures [10,11], with the fluorinated precursors first prepared via the acid-catalyzed condensation of 2-fluorobenzaldehyde and the appropriate diamine. Controlled addition of lithium 2,6-diisopropylphenylamide or lithium cyclohexylamide to the fluorinated precursor at À35 C promoted a metathesis reaction, forming the desired products in good yield.…”
Section: Resultsmentioning
confidence: 99%
“…2,6-diisopropylaniline (90%), benzyl alcohol (99%) and cyclohexylamine were dried over calcium hydride and distilled under a nitrogen atmosphere prior to use. N,N 0 -bis[(2-fluorophenyl)methylene]-1,2-ethanediamine [11], N,N 0 -bis[(2-fluorophenyl)methylene]-1,3-propanediamine [10] and ortho-methylaminobenzaldehyde [16] were prepared via previously published procedures. Dry, reagent grade pentane, tetrahydrofuran and toluene were collected from an Innovative Technologies solvent purification system, consisting of columns containing alumina and a copper catalyst.…”
Section: General Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation